Princetonians. 1784-1790 : a biographical dictionary - Woodward, Ruth L., 1922-; Craven, Wesley Frank, 1905-1981 (Princeton, New Jersey : Princeton University Press, 1991)
These volumes, the fourth and fifth, complete the series of biographical sketches of students at Princeton University (the College of New Jersey in colonial times). They cover pivotal years for both the nation and the College. In 1784, the war with England had just ended. Nassau Hall was still in a shambles following its bombardment, and the College was in financial distress. It gradually regained financial and academic strength, and the Class of 1794 graduated in the year of the death of President John Witherspoon, one of the most important early American educators. The introductory essay by John Murrin, editor of the series since 1981, explores the postwar context of the College. The two volumes contain biographies of 354 men who attended with the classes of 1784 through 1794 and two other students whose presence at the College in earlier years has only now been demonstrated. During these years Princeton accounted for about an eighth of all A.B. degrees granted in the United States. It was the young republic's most "national" college, although it had nearly lost its New England constituency and was instead beginning to draw nearly 40 percent of its students from the South. Originally published in 1991. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- CONTENTS -- LIST OF ILLUSTRATIONS -- PREFACE -- INTRODUCTION / Murrin, John M. -- ABBREVIATIONS AND SHORT TITLES FREQUENTLY USED -- CLASS OF 1784 -- CLASS OF 1785 -- CLASS OF 1786 -- CLASS OF 1787 -- CLASS OF 1788 -- CLASS OF 1789 -- CLASS OF 1790 -- APPENDIX: Geographical and Occupational Listings -- INDEX / Looney, J. Jefferson ; Murrin, John M. ; Woodward, Ruth L.
Online resource; title from PDF title page (EBSCO, viewed September 9, 2015).
Includes bibliographical references and index.
In English.
JSTOR
Keywords: Princeton University -- Alumni and alumnae -- Biography -- Dictionaries; Princeton University -- Alumni and alumnae -- Directories; College of New Jersey (Princeton, N.J.) -- Alumni and alumnae -- Biography -- Dictionaries; College of New Jersey (Princeton, N.J.) -- Alumni and alumnae -- Directories; College of New Jersey (Princeton, N.J.); Princeton University; College students -- United States -- Genealogy; College students -- New Jersey -- Princeton -- Genealogy; New Jersey -- Genealogy; United States -- Genealogy; Étudiants -- États-Unis -- Généalogies.; Étudiants -- New Jersey -- Princeton -- Généalogies.; New Jersey -- Généalogies.; EDUCATION -- Higher; College students; Universities and colleges -- Alumni and alumnae; New Jersey; New Jersey -- Princeton; United States; Biographies; Dictionaries; Directories; Genealogy; Academic catalogs